CHALLENGES IN DIFFERENTIAL DIAGNOSIS IN PRESSURE INJURIES - A CLINICAL CASE REPORT. - Grilo Miranda, Liliana Sofia; Silva Ramos, Paulo Alexandre; Neves Amado, João Daniel; Pereira Alves, Paulo Jorge (Revista Feridas, 2023)
Objectives: To demonstrate the importance of differential diagnosis; to demonstrate the efficiency in the treatment of a category 3 pressure ulcer. Method: Clinical case concerning a 65-year-old female patient, carrier of 2 lesions in the perianal region, with an area of 24cm2 each. Result: After 4 weeks of treatment with ensyme alginogel®, the lesions showed complete healing.Conclusion: Considering PUs an adverse event, they undoubtedly constitute a challenge for healthcare professionals and institutions. The differential diagnosis is essential for the decision in the treatment and prevention of future lesions.